Biological Invasions in South Africa 2020
DOI: 10.1007/978-3-030-32394-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Plant Invasions on Terrestrial Water Flows in South Africa

Abstract: Considerable advances have been made since the first estimates of the impacts of invasive alien plants on water resources in the early 1990s. A large body of evidence shows that invasive alien plants can increase transpiration and evaporation losses and thus reduce river flows and mean annual runoff. Riparian invasions, and those in areas where groundwater is accessible, have 1.2-2 times the impact of invasions in dryland areas. The magnitude of the impacts is directly related to differences between the invadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…We limit our model to the Cape Floristic Region (CFR), a phytogeographic region of 108 677 km 2 encompassing most of the Western Cape province and South Africa's winter and all‐year rainfall regions (Figure S1, Bergh et al, 2014), to take advantage of existing climate interpolations that provide uncertainty estimates (Wilson & Silander Jr., 2014). The approach taken by Le Maitre et al (2016) distills decades of experience and expert knowledge, condensing the existing literature on water use by IAPs into a tractable model for the countries of South Africa, Lesotho and Swaziland (Le Maitre et al, 2020). The impact of IAPs on water resources can be assessed by applying catchment‐level hydrological models to simulate discharge within a region of interest.…”
Section: Methodsmentioning
confidence: 99%
“…We limit our model to the Cape Floristic Region (CFR), a phytogeographic region of 108 677 km 2 encompassing most of the Western Cape province and South Africa's winter and all‐year rainfall regions (Figure S1, Bergh et al, 2014), to take advantage of existing climate interpolations that provide uncertainty estimates (Wilson & Silander Jr., 2014). The approach taken by Le Maitre et al (2016) distills decades of experience and expert knowledge, condensing the existing literature on water use by IAPs into a tractable model for the countries of South Africa, Lesotho and Swaziland (Le Maitre et al, 2020). The impact of IAPs on water resources can be assessed by applying catchment‐level hydrological models to simulate discharge within a region of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, refilling of the SOC stocks through restoration of grasslands does not come at the expense of the productivity at the herbaceous layer and numerous other ecosystem services necessary to meet the demands of local (agro-)pastoralists and other stakeholders. Encroachment of degraded semi-arid grasslands by Prosopis increased the availability of wood and can also refill C stocks, but primarily in the upper 30 cm and at the expense of fodder for livestock and numerous other ecosystem services, including water availability 65,70 . We therefore propose that efforts to reverse land degradation in Baringo and other parts of Sub-Saharan Africa should consider restoration of historical grasslands and their associated ecosystem services and their sustainable embedding in a mosaic of other ecosystems, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Abreu et al 26 showed that fire suppression in savannas of the Brazilian Cerrado increased carbon stocks but was associated with acute biodiversity loss. Similarly, encroachment of degraded tropical grasslands in Baringo by Prosopis increases carbon stocks and the availability of wood, but it threatens biodiversity across multiple trophic levels 64 , increases mosquito densities 68 , reduces the provisioning of herbaceous fodder for grazers 69 and water 65,70 and negatively affects tourism 71 and limits access to water points, pasture, croplands and fishing grounds 72 . In arid and semi-arid regions, the high water consumption by Prosopis is of particular concern, as it decreases the groundwater recharge and thus seriously affects the water available to households in invaded ecosytems 65 .…”
Section: Grassland Management To Create Synergies Between Carbon Sequmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological invasions alter the structure and function of the natural ecosystem, causing the loss of an ecoregion's characteristic species, and may result in loss of indigenous biota (Yang et al, 2015). South Africa has a long history of plant introduction and invasion transforming ecosystems, posing a major threat to the country's biodiversity, impacting negatively on the ecosystem's capacity to deliver goods and services, and in some cases severely threatening human livelihoods (Le Maitre et al, 2020). Alien plant invasion costs the country 2 billion ZAR annually for its control (Van Wilgen et al, 2020;Zengeya and Wilson, 2020).…”
Section: The Effect Of Biological Invasionmentioning
confidence: 99%